Association of environmental, demographic and clinical parameters with physical activity in children with asthma - Jane Berrill; Peter James; Antonis Michanikou; Emmanouil Galanakis; Eleni Michaelidou; Paraskevi Kinni; Nikos Kalivitis; Giorgos Kouvarakis; Emily Vasiliadou; Chrysanthos Savvides; Filippos Tymvios; Petros Koutrakis; et al. (Scientific Reports)
Abstract Personal characteristics, unfavorable weather conditions and air pollution have been linked with reduced physical activity in children. However, among children with asthma the effects of these parameters remain unclear. This study objectively quantified the physical activity of children with asthma and evaluated its association with environmental, personal, and clinical parameters. Participants of the prospective LIFE-MEDEA asthma study wore the EMRACE™ smartwatch daily for continuous monitoring of physical activity and acquisition of global positioning system data. Daily physical activity, personal and clinical data were combined with daily temperature, precipitation, and air pollution levels in adjusted mixed effect regression models to examine the relationship between physical activity and the examined parameters. For a follow-up period of 4 months, 186 children with asthma demonstrated a decrease of 796 steps (95% CI: -1080, -512) on days with precipitation compared to non-precipitation days and a decrease of 96 steps (95% CI: -182, -9) for every 10 µg/m3 increase in PM10. The relationship between temperature and daily steps was characterized by an inverted U-shape. There was also evidence that gender and age-adjusted BMI z-score were negatively associated with daily steps. These results can further inform the design of physical activity interventions targeting children with asthma.